2013
DOI: 10.4103/0019-5413.106898
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic evaluation of femoral component rotation in total knee arthroplasty

Abstract: Background:Optimal femoral component rotational alignment in total knee arthroplasty (TKA) is crucial to establish a balanced knee reconstruction. Unbalanced knees can lead to instability, patellofemoral problems, persistent pain, stiffness, and generally poorer outcomes including early failure. Intraoperative techniques to achieve this optimal femoral component rotation include the use of the transepicondylar axis (TEA), the posterior-condylar-cut-parallel-to-the-tibial-cut (PCCPTC) technique and the anteropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…Despite the simplicity and reproducibility of this method, it may lead to considerable rotational malalignment due to interindividual variations in anatomy (Victor, 2009;Talbot et al, 2017Talbot et al, , 2015. These individual variations have been shown in knees with coexistent distortion of the posterior condylar anatomy, coronal plane varus/valgus knees, morphological and or/disease-related changes, racial and geographical variations and sex, possibly due to individualized body frame (Yoshioka et al, 1987;Poilvache et al, 1996;Griffin et al, 1998;Nagamine et al, 1998;Olcott and Scott, 2000;Akagi et al, 2001;Barrack et al, 2001;Yoshino et al, 2001;Yip et al, 2004;Mullaji et al, 2009;Victor et al, 2009;Victor, 2009;Yue et al, 2011;Mahfouz et al, 2012;Zhang et al, 2012;Vaidya et al, 2013;Daines and Dennis, 2014;Kobayashi et al, 2014;Moghtadaei et al, 2015;Pun et al, 2015;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the simplicity and reproducibility of this method, it may lead to considerable rotational malalignment due to interindividual variations in anatomy (Victor, 2009;Talbot et al, 2017Talbot et al, , 2015. These individual variations have been shown in knees with coexistent distortion of the posterior condylar anatomy, coronal plane varus/valgus knees, morphological and or/disease-related changes, racial and geographical variations and sex, possibly due to individualized body frame (Yoshioka et al, 1987;Poilvache et al, 1996;Griffin et al, 1998;Nagamine et al, 1998;Olcott and Scott, 2000;Akagi et al, 2001;Barrack et al, 2001;Yoshino et al, 2001;Yip et al, 2004;Mullaji et al, 2009;Victor et al, 2009;Victor, 2009;Yue et al, 2011;Mahfouz et al, 2012;Zhang et al, 2012;Vaidya et al, 2013;Daines and Dennis, 2014;Kobayashi et al, 2014;Moghtadaei et al, 2015;Pun et al, 2015;Zhang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Unbalanced knees can lead to instability, patellofemoral problems, persistent pain, stiffness, and generally poorer outcomes including early failure. 23 Although the desired positions and guiding landmarks for placement of the femoral and tibial components in the coronal and sagittal planes have been well described, rotational positioning of the components can still be problematic. 24,25,26 Performing a TKA requires the accurate execution of key bone cuts in the correct orientation to the appropriate axes.…”
Section: Discussionmentioning
confidence: 99%
“…11,31 However, recent biomechanical analyses using instant centers of motion analysis have suggested that the TEA parallels the primary center of rotation of the knee joint but not the posterior condylar axis. 23 The fixed axis that closely approximate the epicondylar axis reported is the TEA has currently attracted attention as an ideal rotational reference that provides functional kinematics (31 Doro LC). Furthermore, several authors also reported that the TEA most consistently recreates a balanced flexion gap.…”
Section: Discussionmentioning
confidence: 99%
“…Balancing was done first in extension using spacer blocks. For creation of a rectangular flexion space, posterior condyle cut parallel to tibial condyle or the “gap balancing” technique was used, the efficacy of which has been published by the lead author 10. This is a modification of the original gap-balancing technique.…”
Section: Methodsmentioning
confidence: 99%